2007
DOI: 10.1128/jvi.01264-07
|View full text |Cite
|
Sign up to set email alerts
|

A Human Lung Carcinoma Cell Line Supports Efficient Measles Virus Growth and Syncytium Formation via a SLAM- and CD46-Independent Mechanism

Abstract: Measles virus (MV) propagates mainly in lymphoid organs throughout the body and produces syncytia by using signaling lymphocyte activation molecule (SLAM) as a receptor. MV also spreads in SLAM-negative epithelial tissues by unknown mechanisms. Ubiquitously expressed CD46 functions as another receptor for vaccine strains of MV but not for wild-type strains. We here show that MV grows and produces syncytia efficiently in a human lung adenocarcinoma cell line via a SLAM-and CD46-independent mechanism using a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 49 publications
4
71
0
Order By: Relevance
“…A number of recent studies investigating MV infection of epithelial cells have focused on in vitro model systems (Tahara et al, 2008;Takeda et al, 2007) or have utilized the macaque model of measles in the absence of histological or pathological analysis of MV-infected tissues (Leonard et al, 2008). These studies have identified specific amino acids of the MV haemagglutinin (H) glycoprotein that are involved in the binding of H to a putative receptor (EpR) on the basolateral surface of epithelial cells and suggest a critical role for epithelial cells in mediating MV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies investigating MV infection of epithelial cells have focused on in vitro model systems (Tahara et al, 2008;Takeda et al, 2007) or have utilized the macaque model of measles in the absence of histological or pathological analysis of MV-infected tissues (Leonard et al, 2008). These studies have identified specific amino acids of the MV haemagglutinin (H) glycoprotein that are involved in the binding of H to a putative receptor (EpR) on the basolateral surface of epithelial cells and suggest a critical role for epithelial cells in mediating MV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…10 An unidentified receptor (EpR) is used by MV in late stages of infection, when MV infects airway epithelial cells and sheds from the respiratory system. 7,11,12 We hypothesized that lentiviral vectors pseudotyped with the envelope proteins of WT MV will exhibit the tropism of clinical MV isolates, that is use SLAM and EpR for cell entry. The data show that MV WT -HIV vectors exhibit a restricted tropism for activated lymphocytes and epithelial cells and can be generated at substantially higher titers than MV Vac -HIV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that vaccine strains are able to use CD46 and CD150/SLAM for cell entry, whereas wild-type strains can use only CD150/SLAM; this is in agreement with the well-known lymphotropism of MV wild-type infections in vivo (for a review see Yanagi et al, 2006). In addition to CD46 and CD150/SLAM, there is evidence for an additional receptor on epithelial cells (Tahara et al, 2008;Takeda et al, 2007).…”
Section: Introductionmentioning
confidence: 64%